Towards a shared anthropology. Reflections, experiences and proposals on participatory photography in anthropological research - González Granados, Paula (Revista de Antropología Social, 2016)
This article has two main objectives. Firstly, to portray the diverse collaborative photography and video experiences in Anthropology. Secondly, to contextualize and share the results of recent research on participatory photography projects promoted by documentary photography collectivities. To this end, I have focused on pioneering works and authors who have tested these methodologies with children and adolescents who are the subject of my fieldwork. This research, which is at a commencing stage, aims to establish synergies with other professionals and therefore establish theories and collaborations in regards to future applied research projects through the use of audiovisual media.